Application of Brazilian semiarid fruits in kefir-based food products: a systematic review (Research, Society and Development, 2021)
The aim of this study was to compile and analyze publications that applied fruits recognized as native and/or cultivated in the Brazilian semiarid region in the development of products obtained from the fermentation of kefir grains. This is a systematic review that used the descriptors ‘kefir’, ‘fruit’, ‘Northeastern Brazil’, ‘semi-arid’, ‘Caatinga biome’ in the databases Google Scholar, LILACS, CAPES Periodicals Portal, Science Direct, SciELO and PubMed, indexed in isolation and associated with Boolean operators ‘and’ and ‘or’, in Portuguese, English and Spanish languages. The search identified 15.017 articles analyzed using a set of criteria that previously considered the title and keywords, abstract, methodology and later, the full reading. The review included a total of 22 articles that met the eligibility criteria, of which 50% (n=11) were in Portuguese, and 27.3% (n=6) with locus in the Northeast region. All selected studies presented results between medium and high methodological quality. The fruits applied were pineapple, açaí, banana, cocoa, coconut, guava, soursop, jabuticaba, lemon, mango, mangaba, papaya and umbu, in the form of pulp, juice, extract, sugar, jam and flour. The studies make inferences about the contributions resulting from the addition of fruits in the characteristics presented in the products, besides pointing out a high market potential. Thus, the use of Brazilian semiarid fruits in fermented kefir products is recent and progressive, the number of studies shows that its application is expanding and, therefore, should be the target of new studies as a promising alternative in the food market potentially functional.